Some considerations regarding the disciplinary nature of modern biology - Macedo-Bedoya, Jehoshua (2024)
The following text discusses the ethical considerations in biology, it highlights the significance of responsible specimen collection methods to minimize the impact on populations. The text also draws attention to the lack of ethical consideration in capture and preservation, as well as the disconnection with contemporary social needs. Additionally, it explores the ethical dilemma surrounding taxonomic accumulation and animal experimentation, with a focus on animal welfare. It advocates for an ethical approach that recognizes the intrinsic value of life and promotes a more holistic perspective in biology.